Phenomenon of medical culturePart 1. Methodological aspect of medical culture - N. A. Khlystova (Бюллетень сибирской медицины)
Medical activity, which always includes the necessity to solve a system of logical, gnoseological, axiological, and praxiological problems associated with the process of diagnostics and treatment of a patient, can be successful only with high culture of a specialist. It is a moral obligation of a medical practician to become a man of culture. Based on a systematic approach, the paper presents medical culture as a specific subsystem of general culture, whose mastering starts in childhood, develops in university, and continues for the whole life, demanding colossal mental energies. In Part 1, the emphasis is at methodological culture of a doctor, and logics of description, definition, and explanation of a studied object or process is presented.